2015
DOI: 10.1007/s00294-014-0472-8
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae as a model for the study of extranuclear functions of mammalian telomerase

Abstract: The experimental evidence from the last decade made telomerase a prominent member of a family of moonlighting proteins performing different functions at various cellular loci. However, the study of extratelomeric function(s) of the catalytic subunit of mammalian telomerase (TERT) is often complicated by the fact that it is sometimes difficult to distinguish them from its role(s) at chromosomal ends. Here we describe an experimental model for studying extranuclear function(s) of mammalian telomerase in the yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Simple organisms such as budding and fission yeast have contributed enormously to our understanding of telomere biology (Simonicova et al 2015;Millet and Makovets 2016;Gadaleta et al 2016). A number of studies in Saccharomyces cerevisiae identified mutants that affect telomere length.…”
Section: Sus1 Interacts Physically and Genetically With Genes Affectimentioning
confidence: 99%
See 1 more Smart Citation
“…Simple organisms such as budding and fission yeast have contributed enormously to our understanding of telomere biology (Simonicova et al 2015;Millet and Makovets 2016;Gadaleta et al 2016). A number of studies in Saccharomyces cerevisiae identified mutants that affect telomere length.…”
Section: Sus1 Interacts Physically and Genetically With Genes Affectimentioning
confidence: 99%
“…Yeast cells provide an excellent model to study mechanisms that affect telomere biology (Askree et al 2004;Simonicova et al 2015;Machin et al 2016;Millet and Makovets 2016;Gadaleta et al 2016). Proteins located at the nuclear periphery in close proximity to TREX-2 have been implicated in genome integrity by protecting the telomeric repeats from recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Their disparate canonical functions and the wide range of moonlighting activities are astonishing and show the power of evolution to produce new functions from extant materials. The biochemical and genetic potentialities of yeasts emphasize their importance in studying moonlighting functions, not only of yeast proteins but also of proteins from other organisms, as shown by Simonicova et al (104), who used S. cerevisiae to study extratelomeric functions of mammalian telomerase.…”
Section: Final Remarks and Perspectivesmentioning
confidence: 99%
“…(reviewed in Gasch 2007 ). Mammalian telomerase expressed in yeast has also been suggested to protect their genome from oxidative stress (Simonicova et al 2015 ). How much do chromosome VIII aneuploids resemble cells with ESR activated?…”
Section: Resultsmentioning
confidence: 99%